Changes in the micro-circulation of skeletal muscle due to varied isometric exercise assessed by contrast-enhanced ultrasound - Krix, Martin; Weber, Marc-André; Kauczor, Hans-Ulrich; Delorme, Stefan; Krakowski-Roosen, Holger (European journal of radiology, 2010)
Purpose - To quantitatively assess local muscle micro-circulation with real-time contrast-enhanced ultrasound (CEUS) during different exercises and compare the results with performed muscle work and global blood flow. - Materials and methods - Sixteen low mechanical index CEUS examinations of the right lower leg flexors of healthy volunteers were performed using a continuous infusion of SonoVue® (4.8mL/300s). Several muscle perfusion parameters were extracted from derived CEUS signal intensity time curves during different isometric exercises (10-50% of maximum individual strength for 20-30s) and then correlated with the performed muscle work or force, and the whole lower leg blood flow which we measured simultaneously by venous occlusion plethysmography (VOP). - Results - The shapes of the CEUS curve during and after exercise differed individually depending on the performed muscle work. The maximum blood volume MAX was observed only after exercise cessation and was significantly correlated with the performed muscle force (r=0.77, p<0.0001). The blood volume over exercise time was inversely correlated with the spent muscle work (r=−0.60, p=0.006). CEUS and VOP measurements correlated only at rest and after the exercise. During exercise, mean CEUS local blood volume decreased (from 3.48 to 2.19 (∼mL)), while mean VOP global blood flow increased (mean, from 3.96 to 7.71mL/100mg/min). - Conclusion - Real-time low-MI CEUS provides complementary information about the local muscle micro-circulation compared to established blood flow measures. CEUS may be used for a better understanding of muscle perfusion physiology and in the diagnosis of micro-circulation alterations such as in peripheral arterial occlusive disease or diabetic angiopathy.